FAKTOR PENENTU MINAT BERWIRAUSAHA: STUDI PADA MAHASISWA POLITEKNIK NEGERI AMBON - Meghan Selvi Amarya Leuhery; Alexandra Huwae; Alfija; Henny Meylissa Latupeirissa; Anthoneta Telsy Waelauruw; Stevanus Johan Gomies; Saul Ronald Jacob Saleky (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
This study examines the impact of entrepreneurship education, family support, and environmental support on the entrepreneurial intentions of students at Politeknik Negeri Ambon, with gender and field of study as control variables. Using multiple regression analysis, the results show that entrepreneurship education significantly influences entrepreneurial intentions. Most respondents find the educational content relevant to the business world and the teaching methods effective. Family support also positively affects intentions, highlighting the importance of emotional and financial backing. Environmental support, significantly contributes to students’ entrepreneurial intentions through support from friends and mentors. The analysis reveals that gender does not significantly impact entrepreneurial intentions, while students from business-related programs show higher entrepreneurial intentions. Overall, the study underscores the significance of entrepreneurship education and social support in fostering entrepreneurial intentions among students and emphasizes the need for relevant curricula across various fields of study.